The leadership scorecard - Phillips, Jack J. (Elsevier Butterworth-Heinemann, 2004)
Strong leaders are essential to business success, which makes leadership development a business imperative in todays competitive environment. Leaders are needed that can do more than manage - leaders are needed that can make a business great. In addition, there is increasing pressure on organizations to demonstrate the wise investment of development dollars. This requires the effective use of leadership development methods, as well as the ability to demonstrate the success of those methods. The Leadership Scorecard combines an explanation and discussion on best practice leadership development methods and incorporates ROI measurement & evaluation methodology.